Relevansi Pupuh Kasmaran Mocoan Lontar Yusup Banyuwangi dengan Kultur Masyarakat Using : Kajian Antropologi Sastra - Iffah Fauziah Rahardy; Yunika Anggraini (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to explore the relevance of Pupuh Kasmaran Mocoan in Lontar Yusup Banyuwangi to the culture of the Banyuwangi community through a literary anthropology approach. Pupuh Kasmaran Mocoan is part of the literary heritage of East Java and is preserved in Lontar Yusup Banyuwangi, reflecting the cultural values, traditions, and worldview of the local society. The research employed a qualitative descriptive method using reading and data classification techniques based on cultural elements. Data were analyzed by identifying cultural aspects embedded in the text and examining their relevance to the social and cultural life of the Banyuwangi community. The findings reveal that Pupuh Kasmaran Mocoan is not merely a literary work but also a representation of the cultural complexity of Banyuwangi society. It contains various cultural values, including social norms, customs, beliefs, and moral teachings that continue to be relevant in contemporary community life. These findings demonstrate that traditional literary works can serve as important cultural documents for understanding local identity and preserving regional wisdom. The study contributes to a deeper understanding of the cultural elements reflected in Lontar Yusup Banyuwangi and emphasizes the significance of literary anthropology in interpreting traditional literature. Furthermore, the findings provide valuable insights for the preservation and development of regional literature while enriching the discourse on literary anthropology.